Laboratory Experiments on Internal Solitary Waves in Ice-Covered Waters - Carr, Magda; Sutherland, P.; Haase, A.; Evers, K.-U.; Fer, Ilker; Jensen, Atle; Kalisch, Henrik; Berntsen, Jarle; Parau, E.; Thiem, Ø.; Davies, P.A. (Geophysical Research Letters, 2020)
Internal solitary waves (ISWs) propagating in a stably stratified two‐layer fluid in which the upper boundary condition changes from open water to ice are studied for grease, level, and nilas ice. The ISW‐induced current at the surface is capable of transporting the ice in the horizontal direction. In the level ice case, the transport speed of, relatively long ice floes, nondimensionalized by the wave speed is linearly dependent on the length of the ice floe nondimensionalized by the wave length. Measures of turbulent kinetic energy dissipation under the ice are comparable to those at the wave density interface. Moreover, in cases where the ice floe protrudes into the pycnocline, interaction with the ice edge can cause the ISW to break or even be destroyed by the process. The results suggest that interaction between ISWs and sea ice may be an important mechanism for dissipation of ISW energy in the Arctic Ocean. publishedVersion